2015
DOI: 10.1038/srep17950
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of hepatitis B virus basal core promoter and precore mutants in HBeAg-positive chronic hepatitis B patients

Abstract: Mutants in the basal core promoter (BCP) and precore (PC) regions of hepatitis B virus (HBV) genome are associated with the progression of chronic hepatitis B (CHB) infection. However, quasispecies characteristics of naturally occurring mutants in those regions in HBeAg-positive CHB patients has not been well described, partly limited by quantitative assay. This study aimed to develop an Ion Torrent deep sequencing assay to determine BCP and PC mutant percentages in HBeAg-positive CHB patients who were treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Other studies, however, have reported inconclusive results regarding the effect of BCP mutations on HBV replication . These heterogenic results may be explained by testing patients with different disease phases, genotype distributions, and frequency of BCP mutants . It is yet unclear which mechanisms would explain lower HBV‐DNA and HBV RNA level in presence of BCP mutations, but the key may be in HBV RNA packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have reported inconclusive results regarding the effect of BCP mutations on HBV replication . These heterogenic results may be explained by testing patients with different disease phases, genotype distributions, and frequency of BCP mutants . It is yet unclear which mechanisms would explain lower HBV‐DNA and HBV RNA level in presence of BCP mutations, but the key may be in HBV RNA packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Protons released during nucleotide incorporation are detected using an ion sensor, which can measure slight shifts in pH ( Merriman et al, 2012 , Reuter et al, 2015 ). Rapid sequencing runs make these sequencers particularly useful for the targeted detection of viruses in clinical samples like HIV Archer et al, 2012 , Chang et al, 2013 , Gibson et al, 2014 ), hepatitis B virus ( Yan et al, 2015 ), HCV ( Gaspareto et al, 2016 , Marascio et al, 2016 ), and the rapid genome sequencing of several viruses including the toscana virus ( Nougairede et al, 2013 ), polyomavirus ( Anthony et al, 2013 ), porcine reproductive and respiratory syndrome virus ( Kvisgaard et al, 2013 ), orthoreovirus ( Steyer et al, 2013 ), bluetongue virus ( Lorusso et al, 2014 ), rotavirus ( Ndze et al, 2014 ; Nyaga et al, 2014 ), influenza virus ( Van den Hoecke et al, 2015 ) etc. Although, some studies used this technology to study viromes in skin ( Bzhalava et al, 2013 ), ticks ( Tokarz et al, 2014 ; Xia et al, 2015 ), gut virome in piglets ( Karlsson et al, 2016 ) and seals ( Kluge et al, 2016 ), this platform is not the ideal choice for virome study in human clinical samples due to lower outputs.…”
Section: Evolution and Use Of Sequencing Technologies For Virus Metagmentioning
confidence: 99%
“…HBV-related oncogenesis is complex and is influenced by viral characteristics such as genetic variants particularly within the X/basal core promoter (BCP)/pre-core (PC) region and integration into the host chromosomes contributing to genomic instability and hepatocarcinogenesis. Through next-generation sequencing (NGS), our group and others have demonstrated the variability of HBV within CHB carriers either with or without end-stage liver disease (cirrhosis and cancer) ( Yan et al, 2015 ; Lau et al, 2018 ; Wu et al, 2018 ). Moreover, we have shown HBV genome integration in both liver and lymphoid cells in individuals with hepatic and extrahepatic malignancy ( Lau et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%